158k views
2 votes
I am stuck on this please help!

I am stuck on this please help!-example-1
User Sagnik
by
4.6k points

1 Answer

0 votes

Answer:


20 {x}^(3) - 36 {x}^(2) + 7x + 3

Solution,


(5x + 1)(2x - 1)(2x - 3)


= 5x(2x - 1) + 1(2x - 1) * (2x - 3) \\ = (10 {x}^(2) - 5x + 2x - 1)(2x - 3) \\ = (10 {x}^(2) - 3x - 1)(2 x - 3) \\ = 10 {x}^(2) (2x - 3) - 3x(2 x - 3) - 1(2x - 3) \\ = 20 {x}^(3) - 30 {x}^(2) - 6 {x }^(2) + 9x - 2x + 3 \\ = 20 {x}^(3) - 36 {x}^(2) + 7x + 3

Hope this helps..

Good luck on your assignment...

User Yngve Moe
by
4.8k points